Current Issues in Duodenoscope-Associated Infections: Now Is the Time to Take Action - Ha, Junghoon (Clin Endosc, 2015)
A duodenoscope has a very complex structure that contains many small parts which make reprocessing more challenging. The difficulty in cleaning duodenoscopes contributes to a higher risk of infection than that of conventional gastrointestinal endoscopes. However, a duodenoscope shares similar disinfection process with other gastrointestinal endoscopes. Recent outbreaks of carbapenem-resistant Enterobacteriaceae (CRE) infections associated with duodenoscopes used for endoscopic retrograde cholangiopancreatography procedures have raised many concerns worldwide. Duodenoscope-associated infections involving CRE or other multidrug-resistant bacteria pose a great threat to patients undergoing procedures using duodenoscopes and should be dealt with a great concern. Updated guidelines regarding cleaning and disinfection of duodenoscope needs to be developed urgently to prevent transmission of infection and ensure patient safety. Meanwhile, healthcare staff should pay special attention to thorough cleaning and disinfection of duodenoscopes.